Two-Dimensional Metal–Organic Framework Nanostructures and Their Composites in Chemical Warfare Agent Detoxification: A Review - Cheng-an Tao; Shiyin Zhao; Yujiao Li; Jianfang Wang (Crystals)
This review summarizes the application of two-dimensional metal–organic framework (2D MOF) nanostructures and their composites in the detoxification of chemical warfare agents (CWAs). Two-dimensional MOFs, characterized by their high specific surface area, abundant active sites, and structural tunability, exhibit promising catalytic performance in CWA detoxification. Various preparation methods, including top–down exfoliation and bottom–up assembly, are discussed for the synthesis of 2D MOF nanosheets. The catalytic performance of 2D MOFs and their composites in detoxifying CWAs is evaluated, highlighting their advantages in terms of reaction kinetics and ease of recycling. Additionally, the advances and challenges in this field are discussed, aiming to promote further research into and development of 2D MOF-based materials for CWA detoxification.